Cold Induced Sweating Syndrome with Urinary System Anomaly Association - Salim Aljabari; Emily Howard; Todd Bell; Tetyana L. Vasylyeva (Hindawi Limited, 2013)
Mutation in the cytokine receptor-like factor 1 and the cardiotrophin-like cytokine (CRLF1 or CLCF1 genes) phenotypically presents as cold induced sweating syndrome (CISS), which is a rare autosomal recessive disorder. The syndrome is characterized by paradoxical sweating in cold weather, dysmorphic facial features, musculoskeletal deformities, difficulty in feeding, and unexplained recurrent episodes of high-grade fever. We are presenting the first case of CISS with urinary system anomaly, which might relate to CRLF1/CLCF1 complex role in the embryonal nephrogenesis.